THE IMPACT OF ADVANCED ANALYTICS AND AI-DRIVEN INSIGHTS ON DATA-DRIVEN DECISION-MAKING IN MARKETING - Sowmya Kotha , (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article explores the transformative impact of advanced analytics platforms and AI-driven insights on data-driven decision-making in marketing. It examines how cutting-edge technologies like Google Analytics 4 and Adobe Experience Platform are revolutionizing customer behavior analysis, audience targeting, and campaign performance measurement. The article delves into the capabilities of these platforms, including real-time behavior tracking, predictive modeling, and personalization at scale. It discusses how AI-powered insights are accelerating decision-making processes and enabling more agile marketing strategies. The research also addresses the optimization of marketing strategies through data-informed budget allocation, AI-based content optimization, and real-time data utilization. While highlighting the immense potential of these technologies, the article acknowledges challenges such as data privacy concerns, skills gaps in analytics interpretation, and the need to balance automation with human intuition. Looking ahead, the paper considers emerging trends in marketing analytics, potential advancements in AI-driven insights, and the integration of analytics with other marketing technologies. Through a comprehensive examination of current practices, challenges, and future directions, this article provides a thorough understanding of how advanced analytics and AI are reshaping the landscape of marketing decision-making and strategy formulation.